I manoscritti etiopici della Biblioteca Statale di Montevergine a Mercogliano, Avellino - Alessandro Bausi (Aethiopica, 2023)
The Biblioteca Statale di Montevergine annexed to the Monumento nazionale di Montevergine, housed in the Palazzo abbaziale di Loreto, in Mercogliano, Avellino, also includes two Ethiopic manuscripts that once belonged to the ‘Johannowsky Library’. The manuscripts date to the nineteenth (non post 1895 CE, Cod. 24, Praise of Mary and Gate of Light) and to the beginning of the twentieth century (1907/1908 CE, Ms. 3, Image of the Twenty-Four Heavenly Priests and Ethiopian Psalter). The first manuscript was apparently taken from the field tent of Rās Mangašā after the Battle of Saganayti, on 15 January 1895, and eventually donated on 27 November 1900 by Daǧāzmāč Mikāʾel to the Italian colonial officer Ilario Capomazza.